Manajemen Kurikulum Terpadu di Pondok Pesantren Modern Daarul Huda Banjar - Hakim, Abdul; Herlina, N. Hani (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
This article is the result of research at Pondok Pesantren Modern Daarul Huda, Banjar City, West Java Province. The results of the research show that: (1) Integrated curriculum planning includes the program of faith development, noble character, science, nationality and nationality, art, entrepreneurship and technical skills, dakwah and community, leadership and management, teacher training, gender equality education, and health, tahfidz al-Qur'an; (2) curriculum structure consists of intra-curricular curriculum, co-curricular and extracurricular; (3) the implementation of integrated curriculum management in this institution is combining several curriculum types such as the formal government curriculum and curriculum of pondok pesantren